Phylogeny and morphologic evolution of the Ordovician Camerata (Class Crinoidea, Phylum Echinodermata). (9th February 2017) - Cole, Selina R.
Abstract: The subclass Camerata (Crinoidea, Echinodermata) is a major group of Paleozoic crinoids that represents an early divergence in the evolutionary history and morphologic diversification of class Crinoidea, yet phylogenetic relationships among early camerates remain unresolved. This study conducted a series of quantitative phylogenetic analyses using parsimony methods to infer relationships of all well-preserved Ordovician camerate genera (52 taxa), establish the branching sequence of early camerates, and test the monophyly of traditionally recognized higher taxa, including orders Monobathrida and Diplobathrida. The first phylogenetic analysis identified a suitable outroup for rooting the Ordovician camerate tree and assessed affinities of the atypical dicyclic family Reteocrinidae. The second analysis inferred the phylogeny of all well-preserved Ordovician camerate genera. Inferred phylogenies confirm: (1) the Tremadocian genera Cnemecrinus and Eknomocrinus are sister to the Camerata; (2) as historically defined, orders Monobathrida and Diplobathrida do not represent monophyletic groups; (3) with minimal revision, Monobathrida and Diplobathrida can be re-diagnosed to represent monophyletic clades; (4) family Reteocrinidae is more closely related to camerates than to other crinoid groups currently recognized at the subclass level; and (5) several genera in subclass Camerata represent stem taxa that cannot be classified as either true monobathrids or true diplobathrids. The clade containing Monobathrida and Diplobathrida, as recognized herein, is termed Eucamerata to distinguish its constituent taxa from more basally positioned taxa, termed stem eucamerates. The results of this study provide a phylogenetic framework for revising camerate classification, elucidating patterns of morphologic evolution, and informing outgroup selection for future phylogenetic analyses of post-Ordovician camerates.